2020
DOI: 10.1128/mbio.03141-19
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Host Cell Surface Protein Disulfide Isomerase by Anaplasma phagocytophilum Asp14 Enables Pathogen Infection

Abstract: Diverse intracellular pathogens rely on eukaryotic cell surface disulfide reductases to invade host cells. Pharmacologic inhibition of these enzymes is cytotoxic, making it impractical for treatment. Identifying and mechanistically dissecting microbial proteins that co-opt surface reductases could reveal novel targets for disrupting this common infection strategy. Anaplasma phagocytophilum invades neutrophils by an incompletely defined mechanism to cause the potentially fatal disease granulocytic anaplasmosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…phagocytophilum infection of neutrophils. The study also showed that the reductase activity of PDI was critical to facilitate this infection (27)…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…phagocytophilum infection of neutrophils. The study also showed that the reductase activity of PDI was critical to facilitate this infection (27)…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this hypothesis, in parasites such as Schistosoma mansoni and Leishmania major, secreted PDIs have been suggested to facilitate parasite-host interactions conducive to successful infection of the host (26). A recent study by Green et al (27) has shown that a membrane bound PDI on mammalian neutrophils binds an Anaplasma phagocytophilum surface protein Asp14 and facilitates A.…”
Section: Discussionmentioning
confidence: 89%
“…EplA exhibits 28.2% identity and 66.9% similarity to Asp14 and 76.7% identity and 92.3% similarity to Ecaj_0636. EplA residues 95-104 and Ecaj_0636 amino acids 89-98 align with Asp14 residues 113-124 (Asp14 113−124 ) that constitute the adhesin's PDI binding domain (Green et al, 2020 ). Because of the importance of Asp14 to A. phagocytophilum infectivity (Kahlon et al, 2013 ; Green et al, 2020 ), the relevance of EplA to E. chaffeensis pathogenesis was examined.…”
Section: Resultsmentioning
confidence: 99%
“…inhibits Trx1 activity-dependent HIV cellular entry (Stantchev et al, 2012). Both antibodies also antagonize A. phagocytophilum infection (Green et al, 2020). The THP-1 cells were incubated with E. chaffeensis DC bacteria and examined for EcVs 24 h later.…”
Section: Host Cell Surface Pdi and Thioredoxin-1 Thiol Reductase Actimentioning
confidence: 99%
See 1 more Smart Citation